Efficient Production of Methyl Oleate Using a Biomass-Based Solid Polymeric Catalyst with High Acid Density - Anping Wang; Heng Zhang; Hu Li; Song Yang (Advances in Polymer Technology)
Biomass-based polymers are eco-friendly, nontoxic and biodegradable materials. In this work, in order to prepare green, low-cost and high-efficient catalysts under mild conditions, we chose biomass-based chitosan as raw material and prepared a new solid acidic catalyst by an acid functionalization method. FT-IR, XRD, SEM, TGA, BET, neutralization titration and other analytical methods were used to characterize the catalyst. The results showed that CS-SO3H morphology exhibited a sphere of about 10 μm diameter, and the acid density was as high as 3.81 mmol/g. The catalyst exhibits good catalytic activity in the esterification of oleic acid and methanol, which is a model reaction of the pre-esterification process in the preparation of biodiesel from feedstocks with high acid values. Under the optimum reaction conditions (15/1 methanol/oleic acid mole ratio and 3 wt% catalyst dosage at 75°C for 3 h), the yield of methyl oleate can reach 95.7%. Even if the mass of oleic acid in the reactant increased to 20 g, solid acid showed good catalytic performance, and the yield of methyl oleate was 94.4%. After four times of reuse, the yield of the catalyst can still reach 85.7%, which indicates that the catalyst has good catalytic activity and stability, and has potential application prospects.